Implementasi Kebijakan Restrukturisasi terhadap Pembiayaan Bermasalah Produk Kredit Pemilikan Rumah pada PT. Bank Sumut - Amri, Khairul; Nurlaila; Syafina, Laylan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
One of the financing products offered by Bank Sumut Syariah Karya Sub-Branch Office is a KPR product. In 2020 most customers took mortgage products, but customers who experienced financing had problems paying installments, especially in 2020 when a pandemic occurred which impacted various sectors including the financial sector. Bank Sumut KCPSy This work has a lot of problematic financing from KPR (Home Ownership Credit) products. In overcoming this, Bank Sumut KCPSy Karya offers financing restructuring to make it easier for customers to pay their obligations. Therefore, this research examines the implementation of non-performing financing restructuring policies on mortgage products (home ownership loans). The method used in this research is descriptive qualitative method. The results of this study show that the implementation of restructuring at the Bank Sumut KCPSy Karya is going well. In implementing the restructuring carried out by Bank Sumut KCPSy it is in accordance with Bank Indonesia Regulation No. 13/9/PBI/2011. The restructuring is carried out by means of reconditioning, namely by reducing the number of installments that must be paid each month for a certain period, without increasing the margin and time period, so that in the period after the restructuring, you have to pay installments that are larger than before. Keywords: Restructuring, Troubled Financing, Home Ownership Loans, PT Bank Sumut Syariah